VAT Dyes as Primary Sensitizers in Occupational Contact Dermatitis: Clinical and Patch Test Profiles in the Traditional Sasirangan Textile Industry - Medisiana Sukses Soenoe; Muslimin; Radityastuti (HM Publisher, 2026)
Background: Occupational contact dermatitis (OCD) significantly impacts workers in the informal textile sector. While disperse dyes are well-documented sensitizers, the allergenic potential of VAT dyes in traditional manufacturing, such as the Indonesian Sasirangan batik industry, remains under-evaluated. Methods: An analytical observational cross-sectional study was conducted on 40 Sasirangan artisans (20 wet workers, 20 dry workers). Clinical diagnoses were established using the Mathias criteria and NOSQ-2002. Epicutaneous patch testing was performed using a baseline series and specific synthetic dyes (1% in petrolatum), read at 48, 72, and 96 hours per ICDRG criteria. Multivariable logistic regression complemented the primary statistical analysis to assess predictive risk factors. Results: The prevalence of positive patch tests was 62.5% (25/40). The primary sensitizers were VAT dye willanthrene brill rose 4R (42.5%) and VAT dye willanthrene green B (37.5%). A significant correlation was found between a clinical history of OCD and positive patch test outcomes (p=0.014, OR=5.6). Surprisingly, job type (wet vs. dry), handwashing frequency, and PPE use did not significantly correlate with patch test positivity (p>0.05), highlighting the pervasive nature of dye allergens across the workspace. Conclusion: VAT dyes are potent primary sensitizers in the traditional Sasirangan textile industry. A clinical history of OCD is a strong predictor of patch test positivity, emphasizing the need for targeted allergen identification and barrier protection.